A theoretical study on lidocaine solubility in deep eutectic solvents. Issue 43 (25th October 2018) - Gutiérrez, Alberto; Atilhan, Mert; Aparicio, Santiago
Abstract : The solvation of lidocaine in two selected deep eutectic solvents is studied using density functional theory and molecular dynamics methods. Abstract : The solvation of lidocaine in two selected deep eutectic solvents is studied using density functional theory and molecular dynamics methods. The intermolecular forces between lidocaine and the involved molecules are analysed in terms of van der Waals and hydrogen bond interactions. The structure, composition and properties of the lidocaine solvation shells are analysed together with the possible lidocaine clustering. The changes in the solvent structures upon lidocaine solution are also studied. The reported results show that the effective solvation of lidocaine in deep eutectics is because of strong solute–solvent intermolecular interactions accompanied by a slight volume expansion and minor solvent structural changes, thus confirming deep eutectics as suitable media for developing pharmaceutical applications.